Effect of organic matter and pH on the resistance of Salmonella Typhimurium and Salmonella Derby in scalding water from pig slaughter - Fernandes Inagaki, Jorge Minor; Sereno, Mallu Jagnow; Pegoraro, Kadigia; Waz, Mykaella Zanatta; Soares, Vanessa Mendonca; Pereira, Juliano Goncalves [UNESP]; Bersot, Luciano dos Santos (Wiley-Blackwell, 2018)
The thermal resistance of Salmonella Typhimurium and Derby was evaluated simulating the pig slaughter scalding process in water with different pH values and organic matter concentrations. In samples of scalding water tanks collected at 0, 2, and 4hr during the slaughter, Salmonella serotypes were quantified at 0, 1, 3, and 5min of heating at 62 degrees C. Variations of water with different pH levels and organic matter contents were also analyzed. A general reduction of 3.19 log CFU/mL in the scalding water and a D value of 1.65min was observed. Salmonella was more sensitive to hot water in an alkaline pH, and the organic matter was not able to interfere with the survival of Salmonella. We conclude that the accumulation of organic matter in the scalding process was not relevant for the survival of Salmonella and that the water alkalinization was important in improving the elimination of this microorganism. Practical applicationsTo know the behavior of Salmonella in different stages of pig slaughter is important for establishing parameters of process, limits, or actions in the control of the contamination program. This study may contribute novel predictions about Salmonella elimination in the scalding stage and provide evidence about factors that can modify the kinetics of reduction, such as the accumulation of organic matter in the scalding tank during the slaughter of pigs and the different pH levels of the water used in this process. This article demonstrated that the addiction of calcium oxide to the scalding water may contribute to the control of Salmonella in the scalding process by reducing the destruction time.